Comparison of the Thermal Loads for Buildings Erected at Four Different Locations in Cyprus - Kalogirou, Soteris A.; Florides, Georgios A.; Evangelou, Evangelos G. (My University, 2003)
Cyprus is an island in the Eastern Mediterranean. Its climate is characterised by abundant sunshine and by moderate to heavy winter conditions. The microclimate though, varies considerably from location to location and is strongly affected by the elevation of a particular location and the proximity to the sea. In this study, four locations are considered which are representative of all the microclimates encountered in Cyprus; coastal, lowland, semimountainous, and mountainous. The weather pattern in these locations presents distinct characteristics. Dry weather with high summer and low winter temperatures are encountered in lowland, high humidity and moderate temperatures in coastal areas whereas dry weather with moderate summer and very low winter temperatures in semi-mountainous and mountainous areas. These weather patterns affect the thermal loads of buildings. A typical house layout with three different construction characteristics is used in this study and is simulated with the TRNSYS program in respect to the heating and cooling loads for a complete year. The weather data file used includes the mean monthly values of ambient air temperature, solar radiation, humidity ratio and wind velocity. TRNSYS Type 54 was used in the simulations in order to generate the hourly weather data required. The results show that the lowland, coastal and semi-mountainous locations exhibit high cooling and heating loads whereas mountainous locations exhibit high heating loads and very low cooling loads.
Keywords: Cyprus; Cooling loads; Heating loads; Buildings